AN INVESTIGATION INTO LINGUISTIC FEATURES OF METAPHOR USES IN ENGLISH AND VIETNAMESE ADVERTISEMENTS - Assoc. Prof. Dr. PHAN VĂN HÒA (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
The thesis aims at investigating conceptual metaphors in English and Vietnamese advertisements, namely through comparison and bilateral contrastiveness, and the author points out the similarities and differences in using conceptual metaphors in English and Vietnamese on linguistic features, namely semantic and lexical features by means of metaphorical expressions. The thesis studies linguistic features of metaphor uses in English and Vietnamese advertisements in the light of the Conceptual Metaphor Theory raised by Lakoff and Johnson (1980) with the famous work “Metaphor We Live By”. The data of the thesis were collected from English and Vietnamese newspapers, magazines, televisions, and internet and contrastively analyzed under qualitative and quantitative approaches. Lastly, suggestions will be drawn on the result analysis in order to apply conceptual metaphors effectively in advertising, learning, and teaching English as a foreign language.